Detection of novel Chlamydiae and Legionellales from human nasal samples of healthy volunteers - Corsaro, Daniele; Venditti, Danielle (Folia microbiologica, 2015)
Chlamydiae are intracellular bacterial parasites of eukaryotes, ranging from amoebae to humans. They comprise many novel members and are investigated as emerging pathogens. Environmental studies highlighted similarities between the ecologies of chlamydiae and legionellae, both groups being important agents of respiratory infections. Herein, we analyzed nasal samples from healthy persons, searching for the presence of amoebae, chlamydiae and legionellae. From a total of 25 samples, we recovered by PCR eight samples positive to chlamydiae and six samples positive to legionellae. Among these samples, four were positive to both organisms. The sequencing of 16S rDNAs allowed to identify (i) among Chlamydiae: Parachlamydia acanthamoebae, Chlamydophila psittaci, Chlamydophila felis, and members of Rhabdochlamydiaceae, Simkaniaceae and E6 lineage and (ii) among Legionellaceae: Legionella longbeachae, Legionella bozemanii and Legionella impletisoli. Unexpectedly, we also recovered Diplorickettsia sp. Amoebae collected from nasal mucosae, Acanthamoeba and Vermamoeba, were endosymbiont-free, and chlamydiae revealed refractory to amoeba coculture. This study shows common exposure to chlamydiae and legionellae and suggests open air activities like gardening as a probable additional source of infection.
Keywords: Sequence Analysis, DNA; RNA, Ribosomal, 16S; DNA, Bacterial; Legionellaceae; Healthy Volunteers; DNA, Ribosomal; Cluster Analysis; Microbiota; DNA bakterií; mikrobiota; protozoální DNA; Amoeba; Nasal Cavity; RNA ribozomální 16S; Humans; nosní dutina; fylogeneze; Chlamydiales; ribozomální DNA; sekvenční analýza DNA; DNA, Protozoan; Phylogeny; shluková analýza; lidé; zdraví dobrovolníci pro lékařské studie